Spanish Validation and adaptation of the Doctor-Patient Relationship Questionnaire (PDRQ-9) in type 2 diabetes mellitus patients in Northern Mexico - Fernández Castillo, Karla Nathalia (Consorcio de Universidades Mexicanas A.C., 2021)
The doctor-patient relationship is an essential predictor of treatment adherence, especially in those diagnosed with a chronic condition such as Type 2 Diabetes Mellitus. The aim of the present investigation was to validate the Patient-Doctor Relationship Questionnaire (PDRQ-9) in a Mexican sample, specifically in Northwest Mexico. This cross-sectional study included 307 Type 2 Diabetes Mellitus patients, who visited a Public hospital. Participants answered the PDRQ-9 as well as an adherence self-report scale individually using an electronic device inside a waiting room of a public health center. To investigate internal consistency and validity, reliability analysis and confirmatory factor analysis were performed. Our results demonstrated that the scale had acceptable reliability (α = 0.95). A confirmatory factor analysis, using Maximum Likelihood method provided evidence of a good fit of the hypothesized one-factor model. All items presented an acceptable acceptable measurement weighs (λ > 0.5). These results show that the adaptation of the PDRQ-9 reproduced the factor structure found in the original study and demonstrated high internal consistency in a Northwest Mexican sample. This study suggests that this instrument is a valid and reliable instrument useful for measuring doctor-patient relationship in patients diagnosed with Type 2 Diabetes Mellitus.